Cyst‐theca relationship of a new dinoflagellate with a spiny round brown cyst, Protoperidinium lewisiae sp. nov., and its comparison to the cyst of Oblea acanthocysta. Issue 2 (1st April 2015) - Mertens, Kenneth Neil; Takano, Yoshihito; Gu, Haifeng; Yamaguchi, Aika; Pospelova, Vera; Ellegaard, Marianne; Matsuoka, Kazumi
Summary: Round spiny brown cysts with apiculocavate processes were isolated from sediments of Lake Saroma, Japan, Changle Harbor, East China Sea, China, Jinzhou Harbor, Bohai Sea, China, and San Pedro Harbor, California, USA. Superficially similar round spiny brown cysts of the species, Oblea acanthocysta were, for comparison, restudied through light microscopy and scanning electron microscopy (SEM) and by sequencing of small subunit (SSU) and large subunit (LSU) rDNA obtained through a single cyst from Lake Saroma. These morphological measurements and SEM observations showed that the new cysts can be discriminated from O. acanthocysta by the archeopyle, number of processes, shape of process bases and its apiculocavate processes . Based on LSU sequences, the most closely related species was Protoperidinium monovelum, for which no cyst stage has been described so far. However, the thecal morphology of the specimens found in this study differed from P. monovelum in details of the sulcal plates and shape of apical pore and 2a plate. We therefore describe Protoperidinium lewisiae sp. nov., which can be found in estuarine subtropical to temperate waters of the Pacific Ocean.